Kernel morphometric traits in hexaploid wheat (Triticum aestivum L.) are modulated by intricate QTL x QTL and genotype x environment interactions - Prashant, Ramya; Kadoo, Narendra Y.; Desale, Charushila; Kore, Prajakta; Dhaliwal, Harcharan Singh; Chhuneja, Parveen; Gupta, Vidya (Journal of Cereal Science, 2012)
Wheat kernel size and shape influence its flour yield and market price. A hexaploid wheat population of 185 recombinant inbred lines was evaluated for five kernel morphometric traits namely, 1000-kernel weight, kernel length, width, length width ratio and factor form density in two diverse agro-climatic regions in India in five to eight year location combinations. Additive main effects and multiplicative interaction analysis revealed significant contributions from genotype (G) and genotype x environment (G x E) effects for these traits. Quantitative trait locus (QTL) analysis by composite interval mapping (CIM) was performed using a linkage map of 251 SSR markers and 59 QTLs distributed on 16 chromosomes were identified. The majority of the QTLs were located on the D genome (44.07%) and the homeologous chromosomes of Group 2 (38.98%). Stable QTLs detected in three or more year location combinations were identified for four traits. Multi-trait CIM showed 10 chromosomal regions harboring putative pleiotropic loci. Complexity in the genetic effects was further revealed by QTL analysis based on mixed-linear model that indicated 19 QTLs with significant individual effects (main-effect QTLs) and 14 QTL x QTL interactions. Five of these - nineteen main-effect QTLs and one of the fourteen QTL x QTL interactions showed environmental influence. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Epistatic QTLs; Genotype x environment interactions; Kernel size and shape; Stable QTLs

Genotype x environment interactions and QTL clusters underlying dough rheology traits in triticum aestivum L. - Prashant, Ramya; Mani, Elangovan; Rai, Richa; Gupta, R. K.; Tiwari, Ratan; Dholakia, Bhushan B.; Oak, Manoj; Roeder, Marion; Kadoo, Narendra Y.; Gupta, Vidya (Journal of Cereal Science, 2015)
Genetic dissection of dough rheology traits (DRT) in hexaploid wheat was carried out using nine mixograph characters evaluated in two consecutive years in three agro-climatic zones in India in an RIL population (HI977 x HD2329). Pearson correlations determined in each year-location indicated 15 stable trait inter-relationships among them but inconsistent correlations with loaf volume (LV) were observed. Using AMMI analysis we derived patterns in G x E interactions (GEI) indicating 6-47% contribution for the DRT. Composite interval mapping using a linkage map of 202 SSR markers identified 144 DRT QTLs of which, 96 were detected in single- and the rest in two to five year-locations. Sixteen QTL clusters located on ten chromosomes were identified and only three of them on chromosomes 1B, 5B and 6D involved LV QTLs. For each trait, majority of the DRT QTLs detected in single as well as multiple environments showed location-specificity and suggested that owing to GEI, breeding for wheat dough quality might need careful selection of QTLs targeted for individual agro-climatic zones. The inconsistent correlations of DRT and LV and differential locations of their QTLs in this population corroborated that using dough rheological traits alone to predict LV might pose challenges during wheat improvement. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: AMMI analysis; Dough rheology; Mixograph; QTL

Exploring the biological roles of Dothideomycetes ABC proteins: leads from their phylogenetic relationships with functionally-characterized Ascomycetes homologs - Dube, Gaurav; Kadoo, Narendra; Prashant, Ramya (PLoS One, 2018)
Background The ATP-binding cassette (ABC) superfamily is one of the largest, ubiquitous and diverse protein families in nature. Categorized into nine subfamilies, its members are important to most organisms including fungi, where they play varied roles in fundamental cellular processes, plant pathogenesis or fungicide tolerance. However, these proteins are not yet well-understood in the class Dothideomycetes, which includes several phytopathogens that infect a wide range of food crops including wheat, barley and maize and cause major economic losses. Results We analyzed the genomes of 14 Dothideomycetes fungi (Test set) and seven well-known Ascomycetes fungi (Model set-that possessed gene expression/functional analysis data about the ABC genes) and predicted 578 and 338 ABC proteins from each set respectively. These proteins were classified into subfamilies A to I, which revealed the distribution of the subfamily members across the Dothideomycetes and Ascomycetes genomes. Phylogenetic analysis of Dothideomycetes ABC proteins indicated evolutionary relationships among the subfamilies within this class. Further, phylogenetic relationships among the ABC proteins from the Model and the Test fungi within each subfamily were analyzed, which aided in classifying these proteins into subgroups. We compiled and curated functional and gene expression information from the previous literature for 118 ABC genes and mapped them on the phylogenetic trees, which suggested possible roles in pathogenesis and/or fungicide tolerance for the newly identified Dothideomycetes ABC proteins. Conclusions The present analysis is one of the firsts to extensively analyze ABC proteins from Dothideomycetes fungi. Their phylogenetic analysis and annotating the clades with functional information indicated a subset of Dothideomycetes ABC genes that could be considered for experimental validation for their roles in plant pathogenesis and/or fungicide tolerance.

Global study of MFS superfamily transporters in arabidopsis and grapes reveals their functional diversity in plants - Patil, Sucheta S.; Prashant, Ramya; Kadoo, Narendra Y.; Upadhyay, Anuradha; Gupta, Vidya S. (Plant Gene, 2019)
The Major Facilitator Superfamily (MFS) is the largest superfamily of secondary transporters present in all organisms, from prokaryotes to higher eukaryotes, that facilitates transport of diverse molecules like sugars, vitamins, amino-acids, hormones, etc. across cell membranes. The superfamily was further expanded to MFS Superfamily (MFSS) to integrate MFS with nine more families. The present study revealed their land plant specific diversity through identification across six species from unicellular alga to higher flowering plants. We identified 71, 131, 254, 260, 213 and 203 MFSS transporters in Chlamydomonas reinhardtii, Physcomitrella patens, Selaginella moellendorffii, Oryza sativa (var. Japonica), Arabidopsis thaliana and Vitis vinifera, respectively and classified them into MFSS families and subfamilies based on their transporter classification identifiers (TCIDs). Detailed analysis of 20 land plant specific subfamilies was conducted in A. thaliana and V. vinifera. Phylogenetic and gene duplication studies revealed the expansion of sugar porter and proton dependent oligopeptide transporter families in Arabidopsis and grape. The subcellular localization of the majority of the transporters was predicted to be in the plasma membrane. Furthermore, the microarray expression analysis of MFSS transporters from Arabidopsis and grapes revealed their multi-tissue-specificity and differential regulation under biotic and abiotic stress conditions. Studies of the transmembrane topology highlighted the presence of central cytoplasmic loop along with family specific topological variations that were evident from phylogenetic analysis. Overall, this study adds to the knowledge of functional and structural diversity and evolution of MFSS transporters in plants and opens the scope for detailed physiological and functional studies on these proteins.

Transcriptomics analysis of propiconazole-treated Cochliobolus sativus reveals new putative azole targets in the plant pathogen - Somani, Deepika; Adhav, Ragini; Prashant, Ramya; Kadoo, Narendra Y. (Functional & Integrative Genomics, 2019)
Cochliobolus sativus (anamorph: Bipolaris sorokiniana) is a filamentous fungus from the class Dothideomycetes. It is a pathogen of cereals including wheat and barley, and causes foliar spot blotch, root rot, black point on grains, head blight, leaf blight, and seedling blight diseases. Annual yields of these economically important cereals are severely reduced due to this pathogen attack. Evolution of fungicide resistant pathogen strains, availability of a limited number of potent antifungal compounds, and their efficacy are the acute issues in field management of phytopathogenic fungi. Propiconazole is a widely used azole fungicide to control the disease in fields. The known targets of azoles are the demethylase enzymes involved in ergosterol biosynthesis. Nonetheless, azoles have multiple modes of action, some of which have not been explored yet. Identifying the off-target effects of fungicides by dissecting gene expression profiles in response to them can provide insights into their modes of action and possible mechanisms of fungicide resistance. Moreover it can also reveal additional targets for development of new fungicides. Hence, we analyzed the global gene expression profile of C. sativus on exposure to sub-lethal doses of propiconazole in a time series. The gene expression patterns were confirmed using quantitative reverse transcriptase PCR (qRT-PCR). This study revealed overexpression of target genes from the sterol biosynthesis pathway supporting the reported mode of resistance against azoles. In addition, some new potential targets have also been identified, which could be explored to develop new fungicides and plant protection strategies.
Keywords: Bipolaris sorokiniana; Cochliobolus sativus; Fungicide resistance; Propiconazole; RNA-seq; Transcriptomics analysis

Comparative proteomics unravels the differences in salt stress response of own-rooted and 110R-grafted thompson seedless grapevines - Patil, Sucheta; Shinde, Manisha; Prashant, Ramya; Kadoo, Narendra; Upadhyay, Anuradha; Gupta, Vidya (Journal of Proteome Research, 2020)
Thompson Seedless, a commonly grown table grape variety, is sensitive to salinity when grown on its own roots, and therefore, it is frequently grafted onto salinity-tolerant wild grapevine rootstocks. Rising soil salinity is a growing concern in irrigated agricultural systems. The accumulation of salts near the root zone severely hampers plant growth, leading to a decrease in the productive lifespan of grapevine and causing heavy yield losses to the farmer. In the present study, we investigated the differences in response to salinity between own-rooted Thompson Seedless (TSOR) and 110R-grafted Thompson Seedless (TS110R) grapevines, wherein 110R is reported to be a salt-tolerant rootstock. The grapevines were subjected to salt stress by treating them with a 150 mM NaCl solution. The stress-induced changes in protein abundance were investigated using a label-free shotgun proteomics approach at three time points viz. 6 h, 48 h, and 7 days of salt treatment. A total of 2793 proteins were identified, of which 246 were differentially abundant at various time-points in TSOR and TS110R vines. The abundance of proteins involved in several biological processes such as photosynthesis, amino acid metabolism, translation, chlorophyll biosynthesis, and generation of precursor metabolites was significantly affected by salt stress in both the vines but at different stages of stress. The results revealed that TSOR vines responded fervently to salt stress, while TS110R vines adopted a preventive approach. The findings of this study add to the knowledge of salinity response in woody and grafted plants and hence open the scope for further studies on salt stress-specific differences induced by grafting.
Keywords: 110R rootstock; gene ontology; grafting; label-free proteomics; salt stress; Vitis vinifera

Whole genome sequencing and comparative genomics of Indian isolates of wheat spot blotch pathogen bipolaris sorokiniana reveals expansion of pathogenicity gene clusters - Yadav, Sagar; Raazi, Zarrine; Shivaraj, Sheelavanta Matha; Somani, Deepika; Prashant, Ramya; Kulkarni, Abhijeet; Kumar, Rajeev; Biradar, Suma; Desai, Shreenivas; Kadoo, Narendra (Pathogens, 2023)
Spot blotch is a highly destructive disease in wheat caused by the fungal pathogen Bipolaris sorokiniana (teleomorph, Cochliobolus sativus). It is prevalent in warm and humid areas, including Africa, Asia, Latin America, and the USA. In the present study, twelve isolates of B. sorokiniana were collected from wheat fields in three different geographical locations in India. The pathogenicity of seven sporulating isolates was assessed on `DDK 1025', a spot blotch-susceptible wheat variety under greenhouse conditions. The isolate `D2' illustrated the highest virulence, followed by `SI' and `BS52'. These three isolates were sequenced using the Illumina HiSeq1000 platform. The estimated genome sizes of the isolates BS52, D2, and SI were 35.19 MB, 39.32 MB, and 32.76 MB, with GC contents of 48.48%, 50.43%, and 49.42%, respectively. The numbers of pathogenicity genes identified in BS52, D2, and SI isolates were 2015, 2476, and 2018, respectively. Notably, the isolate D2 exhibited a relatively larger genome with expanded arsenals of Biosynthetic Gene Clusters (BGCs), CAZymes, secretome, and pathogenicity genes, which could have contributed to its higher virulence among the tested isolates. This study provides the first comparative genome analysis of the Indian isolates of B. sorokiniana using whole genome sequencing.
Keywords: Bipolaris sorokiniana; CAZyme; comparative genomics; spot blotch; whole genome sequencing